P–708 Comparison of reproductive outcomes after progestin-primed ovarian stimulation with dydrogesterone versus cetrorelix to inhibit spontaneous ovulation in oocyte donation. (6th August 2021) - Moreno, J A; Masoli, P; Sferrazza, C; Leiva, H; Espinosa, O; Hernande. . Rudnick, P; Lizardo, J; Rivera, F; Plaz. d. lo. Reyes, S; Cordova, M; Sferrazza, E; Chavez, N; et al.
Abstract: Study question: Is dydrogesterone (DYG) equivalent compared to cetrorelix with respect to clinical pregnancy rate, ongoing pregnancy rate and live birth rate in oocyte donation (OD) cycles? Summary answer: DYG is comparable to cetrorelix in terms of clinical pregnancy, but higher rates of ongoing pregnancy and live birth were observed in the DYG group What is known already: Progestin-primed ovarian stimulation (PPOS) is an ovarian stimulation regimen based on a freeze-all strategy using progestin as an alternative to GnRH analog for suppressing a premature LH surge. DYG is an oral progestin that has been studied in PPOS protocols. Published reports indicate that length of ovarian stimulation, dose of gonadotrophin needed and number of MII retrieved from PPOS cycles are comparable to short protocol of GnRH agonists during OD cycles. However, while some studies noted no differences in terms of live births, worse pregnancy rates have been reported in recipients of oocytes from PPOS cycles compared to GnRH antagonists. Study design, size, duration: Prospective controlled study to assess the reproductive outcomes of OD recipients in which the donors were subjected to the DYG protocol (20mg/day) compared with those subjected to the short protocol with cetrorelix (0.25 mg/day) from Day 7 or since a leading follicle reached 14 mm. The OD cycles were triggered with triptoreline acetate and the trigger criterion was ≥3 follicles of diameter >18mm. Participants/materials, setting, methods: 202 oocyte donors were included, 92 under DYG and 110 under cetrorelix. The study was performed in a private infertility center between January 2017 and December 2020. The main outcome included the rates of clinical pregnancy, ongoing pregnancy and live births. Secondary outcomes included the number of oocytes retrieved, number of MII, fertilization rate, length of stimulation and total gonadotropin dose. Differences were tested using a Student's t-test or a Chi2 test, as appropriate. Main results and the role of chance: Compared to antagonist cycles, cycles under DYG had fewer days of stimulation (9.9 ± 0.9 vs. 10.8 ± 1.1, p<.001) and a lower total gonadotropin dose (1654 ± 402.4 IU vs. 1844 ± 422 IU, p<.001). The number of MII retrieved was no different: 16.9 (SD 6.2) with DYG and 15.4 (SD 5.8) with cetrorelix (p = 0.072). Recipients and embryo transfer (ET) characteristics were also similar between groups. The mean number of MII assigned to each recipients was 6.7 (SD 1.8) in DYG and 6.6 (SD 1.7) in cetrorelix (P = 0.446). The fertilization rate was 66.2% in DYG versus 67.6% in cetrorelix (P = 0.68). Regarding the reproductive outcomes, the overall clinical pregnancy rate in DYG group (65/87: 74.7%) and cetrorelix group (66/104: 63.4%) (p = 0.118) was similar. Meanwhile, the DYG group compared to cetrorelix group had higher rates of ongoing pregnancy (63.2% vs 45.1%; p = 0.014) and live births (54, 9% vs 37.8%; p = 0.040). Limitations, reasons for caution: These results should be evaluated with caution. The limitations of this study include the limited number of participants enrolled and the limited data on pregnancy outcomes. A randomized controlled trial is necessary to provide more evidence on the efficacy of the DYG protocol. Wider implications of the findings: The efficacy of PPOS protocol compared to GnRH-antagonist protocol in terms of reproductive outcomes has been little studied. PPOS using DYG yields comparable clinical pregnancy rates compared to cetrorelix in OD cycles. The differences found regarding the rates of ongoing pregnancy and live births should be further investigated. Trial registration number: Not applicable